Pengembangan dan Pemanfataan iPusnas untuk Masyarakat di Era Milenia - Arief Wicaksono (Jurnal IPI (Ikatan Pustakawan Indonesia), 2022)
scientifically related to its use. The method used is literature review. Subjective analysis was carried out on existing research in the last year when this study was conducted. Subjectivity occurs because the researcher is a librarian at the National Library. The results show that iPusnas, at the age of 3 years, has advantages and disadvantages that are normal. High utilization in the midst of mediocre promotions is an indication that people can make good use of e-books.